2007
DOI: 10.1089/thy.2007.0028
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 and SCD, Markers of Inflammation and Adipogenesis, Are Related to Disease Activity in Graves' Ophthalmopathy

Abstract: We conclude that inflammation and adipogenesis decrease with a decrease in activity of ophthalmopathy and that the nonsteroidal antiinflammatory drug diclofenac inhibits adipogenesis. This may represent a putative future treatment of endocrine ophthalmopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…This is supported by an observation in COX-2 knockout mice where the concentrations of IgM and IgG were reduced by 64 and 35%, respectively, or less as compared to normal controls [19]. We have previously shown that COX-2 is upregulated in orbital tissue of patients with active GO and decreased in the chronic phase [12,14]. COX-2 is an immediate early gene upregulated in response to mitogens, and among this group of genes, regulating inflammation and adipogenesis, CYR61 and EGR-1 have been found to be strongly overexpressed in patients with GO.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…This is supported by an observation in COX-2 knockout mice where the concentrations of IgM and IgG were reduced by 64 and 35%, respectively, or less as compared to normal controls [19]. We have previously shown that COX-2 is upregulated in orbital tissue of patients with active GO and decreased in the chronic phase [12,14]. COX-2 is an immediate early gene upregulated in response to mitogens, and among this group of genes, regulating inflammation and adipogenesis, CYR61 and EGR-1 have been found to be strongly overexpressed in patients with GO.…”
Section: Discussionmentioning
confidence: 64%
“…We have previously shown an overexpression of COX-2 in orbital tissue from GO patients [12]. Approximately one third of the patients with GD will develop clinical GO, but markers for patients at risk are lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, diclofenac reduced the number of mature adipocytes by 50%. This study indicates that diclofenac has potential in the treatment of TED [20]. …”
Section: Clinical Treatmentmentioning
confidence: 92%
“…Otherwise, the gene of proinflammatory cyclooxigenase-2 (COX-2), another partner of the disease, was found overexpressed in severe and active phase of Graves' ophthalmopathy (5,6). According to these data, the use of a PPAR-gamma and COX-2 antagonist could theoretically be useful in the treatment of the orbital disease.…”
Section: Introductionmentioning
confidence: 99%